Interrogating Dispossession for Development in Ethiopia. Issue 1 (2nd January 2022) - Tesema, Yonas
Abstract : In this article, I explore some of the implications of state land policy as an approach to analyzing the double dispossession – land and labor dispossessions. Despite a growing interest in the study of land dispossession in the global South, especially after the post-2008 financial crisis, examining the complexities between the land policy, land and labor dispossessions have relatively been overlooked. I discuss how the state's land policy contributes to coercive land dispossession and how this aspect of dispossession becomes the precondition for the second dispossession – labor. The people who lost their land to investments concurrently lost their employment, and a new class of landless and jobless farmers is emerging.